Defining Criteria for Guiding Cancer Patients to Find a Reputable Complementary Medicine Provider: Results of a Literature Review and a Consensus Procedure - Rogge, Alizé A (Patient Prefer Adherence, 2020)
PURPOSE: Even in cases of positive evidence for complementary medicine (CM) therapies, it is still difficult for cancer patients to identify reputable providers. The aim of this study was to develop and evaluate a criteria list to provide guidance to cancer patients seeking a reputable CM provider. METHODS: The design combined a literature review, an expert consensus procedure (n=15) and an assessment from three stakeholder perspectives (patients (n=18), CM providers (n=26) and oncology physicians (n=20)). RESULTS: A total of 30 existing CM criteria were extracted from the literature, and 12 more were added by the experts. The main challenge was to define criteria that could easily be applied by the patients. A final comprehensive list of 8 criteria guiding cancer patients to find a reputable CM provider was developed. CONCLUSION: Health professionals and cancer information services might find the criteria list helpful when aiming to strengthen patients’ awareness of quality-related factors associated with CM providers. The criteria developed might be helpful when standards are established for quality assurance in CM in oncology.